Children's ways of knowing : learning through experience - Robertson, Margaret, 1948-; Gerber, Rodney (Melbourne, Vic. : ACER Press, 2001)
Following on from 'The Child's World' this title explores how children understand their environment and discusses how to use that understanding as a means of improving education.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Cognition in children; Experience in children; Reasoning in children; Cognition chez l'enfant.; Expérience chez l'enfant.; Raisonnement chez l'enfant.; EDUCATION -- Educational Psychology; Cognition in children; Experience in children; Reasoning in children